Concept of night city: a new dimension to a city’s economy / Saniah Ahmad Zaki and Mohd Riduan Ngesan. - Ahmad Zaki, Saniah; Ngesan, Mohd Riduan (Universiti Teknologi MARA Cawangan Selangor, 2018)
As an outcome of a comprehensive study on an area of 385.401 acres, a township in Alor Gajah, Malacca, was redesigned based on an innovative idea, ‘concept of night city’. The concept is believed to be economically viable. By using space syntax, an analysis of movement as well as the amount of activity likely to result from the movement is performed on the layout to determine if the redesign functions successfully. Results of the spatial analyses showed improvements in connectivity, integration, intelligibility and synergy levels. Based on the ßndings, the future town of Alor Gajah looks viable spatially.